Impacts of large projects on the sediment dynamics and evolution of the Hengsha Shoal in the Yangtze Delta. (1st October 2022) - Yang, H.F.; Li, B.C.; Yang, S.L.; Zhang, Z.L.; Xu, K.H.; Chen, C.P.; Ding, Y.F.; Zhang, W.X.; Shi, B.W.; Wang, Y.P.
Abstract: Global deltas are facing severe challenges under the impacts of riverine sediment decline and large estuarine projects. Comparing with abundant research on the Yangtze subaqueous delta, the shoals in shallow waters are poorly understood. The Hengsha Shoal, Yangtze Delta, China, expands during the past ∼65 years, with only slight changes during the pre-projects period and remarkable variations in the projects period. It's now half-surrounded by the Hengsha Reclamation Project and the Deep Waterway Project, both facilitating the recent expansion. The current vertical net rate of change in the study area is −2.2 cm/yr, suggesting an overall balance between sediment deposition and erosion. Spatially, the Hengsha Shoal is currently changing from horizontal expansion to vertical accretion. Considering the spatial patterns of erosion/deposition and residual currents and sediment, modern geomorphic changes in the Hengsha Shoal appear to be dominated by internal sediment transport from deep to shallow waters. Considering further possible changing conditions, the future evolution of this shoal and the resulting potential ecological impacts should be studied further. This case study demonstrates that sediment dynamics in semi-artificial shoals can be totally different from the subaqueous delta, highlighting the importance of human engineering in governing large deltas globally. Highlights: The Hengsha Shoal expands from slight changes to remarkable alterations. This Shoal is currently changing from horizontal expansion to vertical accretion. This study highlights the importance of engineering in governing deltas globally.